Playground equipment injuries at home versus those in public settings: differences in severity. Issue 2 (16th February 2012) - Keays, Glenn; Skinner, Robin
Abstract : The objective of the present research was to compare the severity of playground-related injuries in backyards of home with those occurring in public settings. This case–control study used emergency-based surveillance data from Canada regarding children, 3–11 years old, who were injured after falling from playground equipment (PGE). Cases were those whose injuries occurred at home (backyards), and controls were those whose injuries occurred in parks, schools or daycare centres. Of the 39 730 subjects selected, 84% happened in public and 16% at home. Children falling from a home PGE had greater odds of severe injuries (OR=1.30; 95% CI 1.23 to 1.37) and fractures (OR=1.47; 95% CI 1.39 to 1.55) than those from public PGE. Children aged 3–5 years falling off slides at home, compared to slides in public settings, had the greatest odds of severe injuries (OR=1.72; 95% CI 1.41 to 2.09) and fractures (OR=2.17; 95% CI 1.79 to 2.64.) When setting up PGE at home, parents should be diligent in using proper landing surfaces, such as those found in public playgrounds.